Emotion-Focused Cognitive Behavioral Therapy in Comorbid Obesity With Binge Eating Disorder: A Pilot Study of Feasibility and Long-Term Outcomes - Torres, Sandra; Sales, Célia M. D.; Guerra, Marina Prista; Simões, Maria P.; Pinto, Mariana; Vieira, Filipa M. (Frontiers in Psychology, 2020)
Obesity coupled with binge eating disorder (BED) is an increasing problem. Incorporation of treatment strategies that address both problems in people with comorbid symptoms is of major interest. This study aimed to investigate the feasibility and preliminary long-term outcomes of a brief emotion-focused cognitive behavioral therapy (EF-CBT) program. Seven out of 10 women with obesity and BED completed the intervention. Standardized outcome measures to assess the intensity of distress caused by complaints, psychological distress, emotional processing, eating behavior, and weight loss were completed at baseline, end-of-treatment, 6- and 18-month follow-ups. Individualized outcome measures were also applied to describe the personal experiences during the intervention. Findings suggest the program’s long-term efficacy for improving psychological distress, emotional processing, and alexithymia. Positive reliable changes in emotional processing and alexithymia were observed in almost all participants. The mean intensity of distress caused by complaints also decreased at the end of the intervention, with a large effect size (d = 0.89). Reliable changes in these outcome measures were observed at all time-points, despite the mean scores for the 18-month follow-up suggest a retraction in improvement. Weight loss was below expectations at all time-points, as were changes in emotional and external eating. Restrained eating mean scores remained stable throughout the study. Participants perceived the program to be useful in improving emotional awareness and eating control. Program feasibility was supported by the retention rate (70%) and the average number of attended sessions (M = 9.71; SD = 2.06). Further studies are needed to examine the effectiveness of EF-CBT interventions.